Malaysia : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
This report provides the analysis of the IMF's projections and estimates for Malaysia on gross domestic product by expenditures and production at constant 1987 prices and at current prices; industrial production index; labor market developments; consumer and producer price indices; federal government revenue and grants; economic and functional classification of federal government expenditure and net lending; federal government operations and fiscal operations; operations of statutory bodies, state, and local governments; general government operations; monetary survey; banking survey; international reserves; balance of payments; interbank swap transactions; developments in Malaysian exchanges during 1996-2000, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet